2018
DOI: 10.1007/s10694-018-0703-5
|View full text |Cite
|
Sign up to set email alerts
|

Fire Performance of Sandwich Panels in a Modified ISO 13784-1 Small Room Test: The Influence of Increased Fire Load for Different Insulation Materials

Abstract: Abstract. Four sandwich panel rooms were constructed as prescribed in the ISO 13784-1 test. However, the construction followed normal industry practice, and the panels were also subjected to the kinds of damage typically found in commercial premises, although such damage may not typically be concentrated in such a small room. The fire load was increased to simulate fires actually occurring in commercial premises by stepping up the propane burner output from the usual maximum of 300-600 kW, and by placing a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Crewe et al 30 In the case of a thermally thick protection such as the plasterboard, it is clearly shown that the peak MLR is below the limit of 2 g·m −2 ·s −1 . At this rate, it is unlikely that self-sustained burning would occur; however, flaming may be achieved under particular conditions as observed in these experiments.…”
Section: Figure 12mentioning
confidence: 99%
“…Crewe et al 30 In the case of a thermally thick protection such as the plasterboard, it is clearly shown that the peak MLR is below the limit of 2 g·m −2 ·s −1 . At this rate, it is unlikely that self-sustained burning would occur; however, flaming may be achieved under particular conditions as observed in these experiments.…”
Section: Figure 12mentioning
confidence: 99%
“…Their results showed that using additional reinforcement can remarkably enhance the ultimate stiffness and strength. Crewe et al (2018) conducted experimental tests on four sandwich panel walls which were made according to ISO 13784-1. The wall thickness was 100 mm with the dimension of 2.43.62.4 as width, length and height, in order.…”
Section: Introductionmentioning
confidence: 99%
“…Here 17,18 showed that fires in commercial premises were often much higher than the prescribed 300 kW and had a longer duration than 30 minutes. Therefore, Leisted 15 added two gas burner regimes with a third burner intensity and two regimes with a continuous burner output to allow for more (severe) testing conditions.…”
mentioning
confidence: 98%